A cross-sectional study of the relationship between sexual compulsivity and unprotected anal intercourse among men who have sex with men in shanghai, China - Xin Wang (BMC Infectious Diseases, 2018)
Abstract Background HIV prevalence among men who have sex with men (MSM) in China is rising rapidly, and unprotected anal intercourse (UAI) is associated with HIV transmission. Recent research has shown that associations between UAI and other factors can differ according to the type of sex partners, including regular partners and casual partners. This study aimed to explore the relationship between sexual compulsivity and UAI according to partner type among MSM in Shanghai, China. Methods A cross-sectional study was conducted among 547 MSM from four districts in Shanghai, China. All participants were recruited using snowball sampling. The Sexual Compulsivity Scale was used to evaluate participants’ sexual compulsivity. Multivariable logistic regression was used to identify factors associated with sexual compulsivity and UAI. The mediation effects of substance use before sex on the relationship between sexual compulsivity and UAI were tested through mediation analyses. Results After adjusting for sociodemographic variables, sexual compulsivity was associated with overall UAI (adjusted odds ratios [AOR] = 1.039, 95% confidence intervals [CI] = 1.004–1.075), UAI with non-regular sex partners (AOR = 1.089, 95% CI = 1.033–1.148) and UAI with commercial sex partners (AOR = 1.185, 95% CI = 1.042–1.349). No significant association was found between sexual compulsivity and UAI with regular sex partners (AOR = 1.029, 95% CI = 0.984–1.077). Mediation analyses indicated that the relationship between sexual compulsivity and UAI was not mediated by either alcohol use before sex or drug use before sex. Conclusions The association between sexual compulsivity and UAI varies depending on the type of UAI partner. Therefore, individuals may engage in different types of UAI for different reasons, and tailored HIV cognitive–behavioral intervention programs are needed.